Visualization and functional analysis of the oligomeric states of Escherichia coli heat shock protein 70 (Hsp70/DnaK) - Thompson, Andrea D. (Springer Netherlands, 2011)
The molecular chaperone DnaK binds to exposed hydrophobic segments in proteins, protecting them from aggregation. DnaK interacts with protein substrates via its substrate-binding domain, and the affinity of this interaction is allosterically regulated by its nucleotide-binding domain. In addition to regulating interdomain allostery, the nucleotide state has been found to influence homo-oligomerization of DnaK. However, the architecture of oligomeric DnaK and its potential functional relevance in the chaperone cycle remain undefined. Towards that goal, we examined the structures of DnaK by negative stain electron microscopy. We found that DnaK samples contain an ensemble of monomers, dimers, and other small, defined multimers. To better understand the function of these oligomers, we stabilized them by cross-linking and found that they retained ATPase activity and protected a model substrate from denaturation. However, these oligomers had a greatly reduced ability to refold substrate and did not respond to stimulation by DnaJ. Finally, we observed oligomeric DnaK in Escherichia coli cellular lysates by native gel electrophoresis and found that these structures became noticeably more prevalent in cells exposed to heat shock. Together, these studies suggest that DnaK oligomers are composed of ordered multimers that are functionally distinct from monomeric DnaK. Thus, oligomerization of DnaK might be an important step in chaperone cycling. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s12192-011-0307-1) contains supplementary material, which is available to authorized users.